2005
DOI: 10.1001/archinte.165.14.1618
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of Vitamin D3 Supplementation in African American Women

Abstract: There was no observed effect of vitamin D(3) supplementation on bone loss or bone turnover markers in calcium-replete, postmenopausal African American women. Further studies are needed to determine if these findings are applicable to women of other ethnic groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
119
2
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(126 citation statements)
references
References 42 publications
1
119
2
4
Order By: Relevance
“…In a study from Norway where Pakistani women were advised to take vitamin D supplements, no improvement in status was shown after 1 year, but whether the advice was followed was not known (3) . A randomised controlled trial of vitamin D supplementation in Ca-replete African-American women did not observe an effect on bone loss or bone turnover markers (30) . The purpose of the present study was to assess the effect of relatively low dosages of supplemental vitamin D on vitamin D status in an immigrant group where sun exposure and vitamin D intake is minimal, and to assess the effect of vitamin D supplementation on bone turnover and bone mass in this group.…”
mentioning
confidence: 92%
“…In a study from Norway where Pakistani women were advised to take vitamin D supplements, no improvement in status was shown after 1 year, but whether the advice was followed was not known (3) . A randomised controlled trial of vitamin D supplementation in Ca-replete African-American women did not observe an effect on bone loss or bone turnover markers (30) . The purpose of the present study was to assess the effect of relatively low dosages of supplemental vitamin D on vitamin D status in an immigrant group where sun exposure and vitamin D intake is minimal, and to assess the effect of vitamin D supplementation on bone turnover and bone mass in this group.…”
mentioning
confidence: 92%
“…However, it has been suggested that these recommendations have been miscalculated, are too low, and should be reconsidered (14). The means and SDs of 25(OH)D for selected large vitamin-D supplementation trials (54)(55)(56)(57)(58)(59)(60) presented in the review by Veugelers et al (13), as well as a trial conducted by our group (57), are presented in Table 6. Three studies used dosages of 400 IU/d with follow-up times of 4, 48, and 108 wk, resulting in mean 6 SD 25(OH)D concentrations of 28.3 6 8.9 ng/mL in healthy men and women (57), and 36.9 6 9.5 ng/mL (56) and 24.4 6 12.2 ng/mL (60) in 2 separate studies of postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…В зарубежных и российских работах были получены аналогичные данные о повыше-нии МПК осевого и периферического скелета, коррекции вторичного гиперпаратиреоидизма и снижении уровня биохимических маркеров костного метаболизма на фоне комбинированной терапии кальцием и витамином D в су-точных дозах от 400 до 800 МЕ [3,9,11,12].…”
Section: Discussionunclassified
“…Кроме того, величина суточной дозы витамина D играет существенную роль в снижении риска переломов. По данным крупных зарубеж-ных исследований, использование витамина D 3 в дозе 800 МЕ в сочетании с солями кальция позволяет снизить риск переломов позвонков на 23-35% [14], шейки бедра -на 29-43% [9,13] и периферических переломов -на 24-32% [9,11]. Столь высокая эффективность препаратов кальция и витамина D наблюдается у пожилых людей с выраженным дефицитом витамина D [3,5,7] и не обнару-живается при нормальном уровне 25(ОН) D в организме, например, у афро-американок [8].…”
Section: Discussionunclassified